Brugada Pattern Type II: A Case Report Highlighting Clinical Challenge in the Early Recognition of Brugada Syndrome - Prastika Dica Izwara; M.Ulil Aidie Jomansyah (Riviera Publishing, 2026)
Background: Brugada syndrome (BrS) is a genetic cardiac channelopathy associated with an increased risk of malignant arrhythmias and sudden cardiac death (SCD), particularly in individuals without structural heart disease. The condition is characterized by specific electrocardiographic (ECG) patterns, with type I showing coved-type ST-segment elevation and type II showing saddleback morphology. Differentiating BrS from Brugada phenocopy (BrP), which is induced by reversible conditions such as electrolyte disturbances, remains a clinical challenge, especially in patients presenting with atypical features. Objective: This case report aims to describe the clinical presentation, diagnosis, and management of a patient with a type II Brugada ECG pattern. Method: A 38-year-old male presented with chest pain, diaphoresis, and syncope. Electrocardiography, laboratory tests, cardiac monitoring, and echocardiography were performed. Results: ECG revealed a saddleback ST-segment elevation ?2 mm in lead V2, consistent with the type II Brugada pattern. Laboratory findings, including electrolytes and troponin I, were normal. Cardiac monitoring recorded premature ventricular contractions. Echocardiography showed normal cardiac function. The Brugada pattern persisted on follow-up ECGs. Conclusion: Early recognition of the type II Brugada pattern is crucial in patients with syncope, even with normal electrolytes. Referral for electrophysiological studies and consideration of an ICD is essential to prevent SCD.